1955
DOI: 10.1161/01.cir.11.4.531
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Myocardial Factors in Rheumatic Heart Disease with Mitral Stenosis

Abstract: Sixteen patients with rheumatic heart disease and pure mitral stenosis, studied by cardiac catheterization, are presented to illustrate the relative importance of mitral block and myocardial insufficiency in this disease. Analysis of hemodynamic data permitted a separation of those patients with predominantly mechanical mitral block from those in whom myocardial insufficiency appeared to be the predominant lesion. The importance of recognizing the existence of the latter group is emphasized, since commissuroto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
4

Year Published

1956
1956
1995
1995

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(33 citation statements)
references
References 6 publications
1
28
0
4
Order By: Relevance
“…Studies in patients with mitral stenosis, before and after valvotomy, confirm that there is a much better correlation between clinical improvement and amelioration of the excessive ventilatory response on the one hand and a fall in pulmonary vascular pressures on the other, than there is with any rise in the cardiac output (Eliasch, 1952;Wade, Bishop, and Donald, 1954;Harvey et al, 1955;Donald et al, 1957). It is noted, however, that Donald and his associates, despite observing a good correlation between resting pulmonary wedge pressure and ventilation, found a very high exercise wedge pressure, sometimes of the order of 50 mm.…”
mentioning
confidence: 99%
“…Studies in patients with mitral stenosis, before and after valvotomy, confirm that there is a much better correlation between clinical improvement and amelioration of the excessive ventilatory response on the one hand and a fall in pulmonary vascular pressures on the other, than there is with any rise in the cardiac output (Eliasch, 1952;Wade, Bishop, and Donald, 1954;Harvey et al, 1955;Donald et al, 1957). It is noted, however, that Donald and his associates, despite observing a good correlation between resting pulmonary wedge pressure and ventilation, found a very high exercise wedge pressure, sometimes of the order of 50 mm.…”
mentioning
confidence: 99%
“…One might postulate that poor ventricular compliance is the reason for the lack of dramatic improvement in this patient. This has been suggested by several investigators in the past (15)(16)(17)(18). The most reasonable explanation for the markedly reduced effect of atrial systole in augmenting stroke volume in patients with severe mitral stenosis is the loss of energy secondary to marked turbulence of blood flowing across the deformed mitral valve.…”
Section: )mentioning
confidence: 89%
“…Many studies have shown that in pure mitral stenosis, the left ventricular function (LVF) impairment is often observed (Bolen et al, 1975;Curry and Elliott, 1972;Ferrer et al, 1952;Flemming and Wood, 1959;Harvey et al, 1955). This LVF impairment can at times be obvious when considering the hemodynamic data at rest (Curry and Elliott, 1972;Herreman et al, 1980;Kennedy et al, 1970), but at other times it becomes evident only when an impairment response of the left ventricle to hemodynamic-induced changes is apparent (Bolen er al., 1975;Linhm, 1972;Ross and Braunwald, 1964).…”
Section: Introductionmentioning
confidence: 99%
“…This LVF impairment can at times be obvious when considering the hemodynamic data at rest (Curry and Elliott, 1972;Herreman et al, 1980;Kennedy et al, 1970), but at other times it becomes evident only when an impairment response of the left ventricle to hemodynamic-induced changes is apparent (Bolen er al., 1975;Linhm, 1972;Ross and Braunwald, 1964). In some patients the failure of mitral surgery to effect a satisfactory improvement can only be the result of a previous LV deficiency (Ferrer et al, 1952;Flemming and Wood, 1959;Harvey et al, 1955). Many factors may be involved in this ventricular dysfunction, such as a "myocardial factor," subvalvular fibrosis and a rigid "mitral complex," or an important reduction of the LV filling (Ferrer et al, 1952;Flemming and Wood, 1959;Grant, 1953;Harvey et al, 1955).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation